Analisis Tindak Kejahatan Siber berdasarkan UndangUndang ITE pada Putusan 616/Pid.Sus/2023/PN Jakarta Selatan - Ashila Raisya Khaliza; Christabel Daniella Suhendra; Naomi Inly; Russel Dante; Serlita Ruben Pendang; Valence Deanthony Dior (Jurnal Hukum Lex Generalis, 2026)
A case involving a public figure in Decision Number 616/Pid.Sus/2023/PN Jakarta Selatan serves as an example of law enforcement against cybercrime in Indonesia. This study aims to analyze the distribution of obscene electronic content based on the Law on Electronic Information and Transactions. The method used is normative legal research with statutory and case approaches. The analysis focuses on the elements of criminal acts, characteristics of cybercrime, and electronic evidence. The results show that such acts fulfill the elements of a criminal offense under the ITE Law and highlight the importance of legal protection for victims in the digital era.